Trapping and Propelling Microparticles at Long Range by Using an Entirely Stripped and Slightly Tapered No-Core Optical Fiber - Yen-Si Huang; Fang-Wen Sheu (Sensors, 2013)
A stripped no-core optical fiber with a 125 µm diameter was transformed into a symmetric and unbroken optical fiber that tapers slightly to a 45-µm-diameter waist. The laser light can be easily launched into the no-core optical fiber. The enhanced evanescent wave of the slightly tapered no-core optical fiber can attract nearby 5-µm-diameter polystyrene microparticles onto the surface of the tapered multimode optical fiber within fast flowing fluid and propel the trapped particles in the direction of the light propagation to longer delivery range than is possible using a slightly tapered telecom single-mode optical fiber.